Infant Can Visually Differentiate the Fresh and Degraded Foods: Evidence From Fresh Cabbage Preference - Yang, Jiale; Okajima, Katsunori; Kanazawa, So; Yamaguchi, Masami K. (Frontiers in Psychology, 2019)
Perceiving and judging food quality is indispensable in daily life. The present study examined this ability’s development in infants during the early postnatal months. We tested if infants aged 5–8 months can discriminate different degree of freshness in cabbage, strawberry, carrot, and spinach. In Experiment 1, images of fresh and degraded vegetables were presented side-by-side; infants aged 7–8 months significantly preferred fresh over degraded cabbage images. In Experiment 2 and 3, infants aged 7–8 months maintained their preference when the images were achromatic, but no longer preferred the fresh cabbage images when pixels in those images were randomized. Given these results, we suggest that the ability to discriminate different degrees of freshness, at least for cabbage, develops at approximately 7–8 months of age, which is the time probably prior to taste learning.